PEMBINAAN KEWIRAUSAHAAN USIA PRA-KERJA DI PANDANTOYO NGANCAR KEDIRI - Fatmah; Nur Arfi Khoriyah; Helmy Erawansyah; Fadia Vallantia Naufa Amaradani; Ratu Hamdiyah Rosyadi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
The aim of the team’s community service was to provide soft skills to the residents of Dusun Gogorejo, Pandantoyo, Ngancar, Kediri. The community service method employed the ABCD approach, which focuses on developing community assets. The results of this activity indicate that the entrepreneurial training program for pre-working-age individuals in Dusun Gogorejo, Pandantoyo, Ngancar, Kediri, had positive outcomes in enhancing participants' knowledge, skills, and motivation. The program also enriched participants' understanding of business opportunities, particularly those based on local potential such as pineapples, and taught effective production techniques and marketing strategies. Furthermore, entrepreneurial motivation and interest increased, as evidenced by participants’ readiness to start new businesses and develop business ideas relevant to local conditions.